New thiadiazine derivatives with activity against Trypanosoma cruzi amastigotes - Muelas, S; Di Maio, R; Cerecetto, H; Seoane, G; Ochoa, C; Escario, J A; Gómez-Barrio, A (Folia parasitologica, 2001)
The cytotoxicity of 18 new 1,2,6-thiadiazin-3,5-dione 1,1-dioxides was evaluated. This group of products was previously assayed against epimastigotes of Trypanosoma cruzi and some of them showed a high antiprotozoal activity. Thereafter 13 compounds with a high anti-epimastigote activity and low cytotoxicity were selected to be assayed against amastigotes. Some of the products showed the same or even lower cytotoxicity than nifurtimox and benznidazole, but most of them were very toxic for macrophages at 100 microg/ml. Only one of the compounds had an anti-amastigote activity similar to that of reference drugs at 10 microg/ml, but unfortunately this disappeared at lower concentrations.
Keywords: antiprotozoální látky; myši; Chagas Disease; parazitické testy citlivosti; Chagasova nemoc; Animals; Trypanosoma cruzi; Antiprotozoal Agents; Macrophages; Mice; Thiadiazines; thiadiaziny; zvířata; makrofágy; Parasitic Sensitivity Tests